Risk Perceptions on Hurricanes: Evidence from the U.S. Stock Market - Feria-Domínguez, José Manuel (Int J Environ Res Public Health, 2017)
This article examines the market reaction of the main Property and Casualty (P & C) insurance companies listed in the New York Stock Exchange (NYSE) to seven most recent hurricanes that hit the East Coast of the United States from 2005 to 2012. For this purpose, we run a standard short horizon event study in order to test the existence of abnormal returns around the landfalls. P & C companies are one of the most affected sectors by such events because of the huge losses to rebuild, help and compensate the inhabitants of the affected areas. From the financial investors’ perception, this kind of events implies severe losses, which could influence the expected returns. Our research highlights the existence of significant cumulative abnormal returns around the landfall event window in most of the hurricanes analyzed, except for the Katrina and Sandy Hurricanes.